2018
DOI: 10.12661/pap.2017.016
|View full text |Cite
|
Sign up to set email alerts
|

Produção da goiabeira (Psidium guajava L.) em sistema convencional e orgânico

Abstract: AgronomiA-FitotecniA Produção da goiabeira (Psidium guajava L.) em sistema convencional e orgânico Guava production (Psidium guajava L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These authors concluded that the use of soil remineralizers promotes increased productivity, in addition to reducing the environmental impacts caused by the overuse of soluble sources of fertilization. These results are consistent with those observed by Malta et al (2018) in guava culture, in which the use of rock powder promoted an increase in fruit pulp and firmness, when compared to the other forms of fertilization tested. Li et al ( 2021) observed an increase in the diversity of microorganisms present in the soil, an increase in apple fruit yield, and a reduction in disease symptoms and fruit fall.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These authors concluded that the use of soil remineralizers promotes increased productivity, in addition to reducing the environmental impacts caused by the overuse of soluble sources of fertilization. These results are consistent with those observed by Malta et al (2018) in guava culture, in which the use of rock powder promoted an increase in fruit pulp and firmness, when compared to the other forms of fertilization tested. Li et al ( 2021) observed an increase in the diversity of microorganisms present in the soil, an increase in apple fruit yield, and a reduction in disease symptoms and fruit fall.…”
Section: Resultssupporting
confidence: 91%
“…Aguilera et al (2022) concluded that it is advantageous to use basalt rock powder in maize crops. Malta et al (2018) who used rock powder in guava culture, found an increase in fruit pulp and firmness, when compared to cultivation only with chemical fertilizers. Li et al (2021) using rock dust from the mining and quarrying industry verified a significant increase in the amount of nutrients such as Ca, Mg, Fe, Mn, Zn, B and Al, compared to the compound without the rock dust, however, without causing phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Esses autores concluíram que a utilização de remineralizadores de solo promovem aumento de produtividade, além de reduzir os impactos ambientais causados pelo excesso de utilização de fontes solúveis de adubação. Resultados estes condizentes aos observados por Malta et al (2018) na cultura da goiaba, em queo uso de pó de rocha promoveu incremento de polpa dos frutos e firmeza, quando comparado as demais formas de…”
Section: Resultados E Discussõesunclassified
“…(2022)concluíram ser vantajoso a utilização do pó de rocha de basalto na cultura do milho. Malta et al (2018) que utilizando pó de rocha na cultura da goiaba, constataram aumento da polpa dos frutos e firmeza dos mesmos, quando comparado ao cultivo somente com as adubações químicas. Li et al (2021) utilizando pó de rocha proveniente de indústria de mineração e pedreira verificaram incremento significativo na quantidade de nutrientes como Ca, Mg, Fe, Mn, Zn, B e Al, comparado ao composto sem o pó de rocha, no entanto, sem causar fitotoxicidade.…”
unclassified
“…The highest water potential values are observed in the morning (7:00 to 8:00 am), while the lowest are verified in the early afternoon (12:00 to 15:00 pm), with sub-sequent rehydration of the plant [2,46,54]. Loss of cellular turgor is one of the first characteristics to appear when the plant is under water deficit, which, among other effects, limits stomatal opening, directly impacting plant gas exchange and causing an increase in leaf temperature [55][56][57].…”
Section: Discussion Fruit Pruning and Thinning Improves Gas Exchange ...mentioning
confidence: 99%